Phase I metabolism of the highly potent synthetic cannabinoid MDMB‐CHMICA and detection in human urine samples. Issue 5 (21st September 2016) - Franz, Florian; Angerer, Verena; Moosmann, Bjoern; Auwärter, Volker
Abstract : Among the recently emerged synthetic cannabinoids, MDMB‐CHMICA (methyl N ‐{[1‐(cyclohexylmethyl)‐1 H ‐indol‐3‐yl]carbonyl}‐3‐methylvalinate) shows an extraordinarily high prevalence in intoxication cases, necessitating analytical methods capable of detecting drug uptake. In this study, the in vivo phase I metabolism of MDMB‐CHMICA was investigated using liquid chromatography‐electrospray ionization‐tandem mass spectrometry (LC‐ESI‐MS/MS) and liquid chromatography‐electrospray ionization‐quadrupole time‐of‐flight‐mass spectrometry (LC‐ESI‐Q ToF‐MS) techniques. The main metabolites are formed by hydrolysis of the methyl ester and oxidation of the cyclohexyl methyl side chain. One monohydroxylated metabolite, the ester hydrolysis product and two further hydroxylated metabolites of the ester hydrolysis product are suggested as suitable targets for a selective and sensitive detection in urine. All detected in vivo metabolites could be verified in vitro using a human liver microsome assay. Two of the postulated main metabolites were successfully included in a comprehensive LC‐ESI‐MS/MS screening method for synthetic cannabinoid metabolites. The screening of 5717 authentic urine samples resulted in 818 cases of confirmed MDMB‐CHMICA consumption (14%). Since the most common route of administration is smoking, smoke condensates were analyzed to identify relevant thermal degradation products. Pyrolytic cleavage of the methyl ester and amide bond led to degradation products which were also formed metabolically. This is particularly important in hair analysis, where detection of metabolites is commonly considered a proof of consumption. In addition, intrinsic activity of MDMB‐CHMICA at the CB1 receptor was determined applying a cAMP accumulation assay and showed that the compound is a potent full agonist. Based on the collected data, an enhanced interpretation of analytical findings in urine and hair is facilitated. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this study the in vivo phase I metabolism of MDMB‐CHMICA was investigated. The detected main metabolites were formed by hydrolysis of the methyl ester and oxidation of the cyclohexyl methyl side chain. Applying a cAMP assay the compound showed to be a potent full agonist at the CB1 receptor. Based on the collected data an enhanced interpretation of analytical findings of the postulated metabolites in urine and hair is facilitated.